Popular culture in the Arab world : arts, politics, and the media - Hammond, Andrew, 1970- (Cairo : American University in Cairo Press, 2007)
Culture and politics in the Arab world today -- The Arabic language : the key to Arab identity -- Popular religion : where 1001 Islams converge -- Arab consumer culture : the packaging of people and places -- Arab cinema and the dream of modernization -- From Umm Kalthum to Arabpop -- The belly dance : a reinvented Arab groove -- Television : from media mobilization to satellite revolution -- The trials and tribulations of the Arabic press -- Arab theater : the struggle for high culture
'An earlier version of this book was published as Pop culture Arab world!: media, arts, and lifestyle in 2004 by ABC-CLIO.'--T.p. verso.
Includes bibliographical references (p. [323]-351) and index.
Keywords: Civilization, Arab -- 21st century; Popular culture -- Arab countries; Mass media -- Arab countries